Beyond Guthrie?: Text-linguistics and New Testament Studies - Rudolph, Michael Allan (Filología neotestamentaria, 2013)
The promise of linguistics for biblical studies has not yet been realized. While the bulk of the biblical, scholarly community has remained aloof and unimpressed, others have pursued this field of study, struggling with unfamiliar and often ill-defined terminology, even as they sought to develop an effective and objective methodology. This paper examines the work of one “eclectic” approach, the “Cohesive Shift Analysis” of George H. Guthrie, acknowledging its contribution, yet also suggesting corrective refinements.